The Vasodilating Effect of Royal Jelly in Rabbit Arteries - Peungvicha, Penchom; Wongkraj ang, Yuvadee; Jaiarj, Pranee (Journal of Basic and Applied Pharmacology, 2015)
Royal jelly was the milky white, highly viscous secretion from the hypopharyngeal glands of the worker honey bees. The vasodilating effect of lyophilized royal jelly was tested in rabbit aorta and femoral arteries in vitro. It was found that the vasomotor tension, induced by the submaximal dose of norepinephrine, was significantly decreased by royal jelly (dissolved in dimethylsulfoxide) at the doses of 1 and 2 mg in 25 ml of kreb's solution (P< 0.05). Furthermore, after adding physostigmine (acetylcholine agonist) about 1 min before royal jelly and norepinephrine at the same dose the tension was more significantly decreased. But after adding atropine or scopolamine (acetylcholine competitive inhibitor) about 1 min before royal jelly and norepinephrine at the same dose, the tension was not different from the dimethylsulfoxide and norepinephrine treated group (P >0.05). The results from this study suggested that royal jelly might inhibit the vasoconstriction via acetylcholine receptors.